Metamorphic labral axis patterning in the beetle Tribolium castaneum requires multiple upstream, but few downstream, genes in the appendage patterning network. Issue 2 (11th March 2014) - Smith, Frank W.; Angelini, David R.; Gaudio, Matthew S.; Jockusch, Elizabeth L.
SUMMARY: The arthropod labrum is an anterior appendage‐like structure that forms the dorsal side of the preoral cavity. Conflicting interpretations of fossil, nervous system, and developmental data have led to a proliferation of scenarios for labral evolution. The best supported hypothesis is that the labrum is a novel structure that shares development with appendages as a result of co‐option. Here, we use RNA interference in the red flour beetle Tribolium castaneum to compare metamorphic patterning of the labrum to previously published data on ventral appendage patterning. As expected under the co‐option hypothesis, depletion of several genes resulted in similar defects in the labrum and ventral appendages. These include proximal deletions and proximal‐to‐distal transformations resulting from depletion of the leg gap genes homothorax and extradenticle, large‐scale deletions resulting from depletion of the leg gap gene Distal‐less, and smaller distal deletions resulting from knockdown of the EGF ligand Keren . However, depletion of dachshund and many of the genes that function downstream of the leg gap genes in the ventral appendages had either subtle or no effects on labral axis patterning. This pattern of partial similarity suggests that upstream genes act through different downstream targets in the labrum. We also discovered that many appendage axis patterning genes have roles in patterning the epipharyngeal sensillum array, suggesting that they have become integrated into a novel regulatory network. These genes include Notch, Delta, and decapentaplegic, and the transcription factors abrupt, bric à brac, homothorax, extradenticle and the paralogs apterous a and apterous b .